Macro policies and the food sector in Bangladesh: a general equilibrium analysis - Fontana, Marzia; Wobst, Peter; Dorosh, Paul A. (International Food Policy Research Institute, 2001)
Trade liberalization in the early 1990s in Bangladesh has enabled the private sector to respond with market-stabilizing inflows of rice and wheat following major production shortfalls. At the same time, easing of restrictions on foreign investment, combined with substantial depreciation of the Taka, have enabled exports of the labor-intensive ready-made garment industry to expand significantly. Moreover, recently discovered natural gas resources might be exploited, creating new revenues for the country. A proper assessment of the impact of such policies and economic developments on the poor requires a comprehensive framework to analyze interactions between different sectors, and linkages between macro and micro levels. In this paper we develop a computable general equilibrium model (CGE) with special treatment of the rice and wheat sectors, and we use it to simulate the impact of (i) a decline in rice production due to floods, (ii) a cut in food aid of wheat, and (iii) increased revenues from the exploitation of natural gas resources. The results suggest that most households benefit from more liberalized rice and wheat trade, particularly after rice production shocks. Impacts of a decline in wheat food aid are relatively modest, as food aid imports are not large enough to have major macroeconomic effects. The simulations of natural gas export revenues suggest that the extent of disincentives to agriculture will depend on whether or not the resulting real exchange rate appreciation is sufficient to lower the import parity price of rice enough so that domestic prices are affected. Finally, all three simulations show that the effects of economic shocks on women’s labor and female headed poor households can differ significantly from the effects on men’s labor and other households.